Capacity, Entry and Forward Induction - Kyle Bagwell; Garey Ramey (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
We introduce avoidable fixed costs into the capacity and entry model of Dixit (1980) to produce a coordination problem among multiple postentry equilibria. Elimination of weakly dominated strategies makes it possible for the entrant to play a knockout strategy, consisting of a large capacity commitment which selects the entrant's preferred postentry equilibrium and drives the incumbent from the market. The incumbent must respond to the knockout threat by using judo tactics, involving a reduction in its capacity commitment. In subgame perfect equilibria which are robust to elimination of weakly dominated strategies, the incumbent must accept a market share smaller than the entrant's if avoidable fixed costs are sufficiently high, or cede the market to the entrant if avoidable fixed costs are higher still.
Keywords: 330